High-Contrast Stimulation Potentiates the Neurotrophic Properties of Müller Cells and Suppresses Their Pro-Inflammatory Phenotype - Zloh, Miloslav; Kutilek, Patrik; Stofkova, Andrea (International journal of molecular sciences, 2022)
High-contrast visual stimulation promotes retinal regeneration and visual function, but the underlying mechanism is not fully understood. Here, we hypothesized that Müller cells (MCs), which express neurotrophins such as brain-derived neurotrophic factor (BDNF), could be key players in this retinal plasticity process. This hypothesis was tested by conducting in vivo and in vitro high-contrast stimulation of adult mice and MCs. Following stimulation, we examined the expression of BDNF and its inducible factor, VGF, in the retina and MCs. We also investigated the alterations in the expression of VGF, nuclear factor kappa B (NF-κB) and pro-inflammatory mediators in MCs, as well as their capacity to proliferate and develop a neurogenic or reactive gliosis phenotype after high-contrast stimulation and treatment with BDNF. Our results showed that high-contrast stimulation upregulated BDNF levels in MCs in vivo and in vitro. The additional BDNF treatment significantly augmented VGF production in MCs and their neuroprotective features, as evidenced by increased MC proliferation, neurodifferentiation, and decreased expression of the pro-inflammatory factors and the reactive gliosis marker GFAP. These results demonstrate that high-contrast stimulation activates the neurotrophic and neuroprotective properties of MCs, suggesting their possible direct involvement in retinal neuronal survival and improved functional outcomes in response to visual stimulation.
Keywords: NF-κB; mozkový neurotrofický faktor; Ependymoglial Cells; neurodifferentiation; BDNF; reactive gliosis; Inflammation; Phenotype; zvířata; myši; zánět; retina; Brain-Derived Neurotrophic Factor; Mice; Retina; Müller cells; ependymální buňky; high-contrast stimulation; fenotyp; Animals; VGF; glióza; Gliosis